2023
DOI: 10.3390/healthcare11030424
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Kidney Stones

Abstract: In the past two decades, major breakthroughs that improve our understanding of the pathophysiology and therapy of kidney stones (KS) have been lacking. The disease continues to be challenging for patients, physicians, and healthcare systems alike. In this context, epidemiological studies are striving to elucidate the worldwide changes in the patterns and the burden of the disease and identify modifiable risk factors that contribute to the development of kidney stones. Our expanding knowledge of the epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 212 publications
0
37
0
1
Order By: Relevance
“…Urolithiasis is the condition in which stones are formed in the urinary tract due to elevated levels of salts in urine. According to studies, almost 2% individuals in their 20s and 30s develop kidney stones (Stamatelou and Goldfarb, 2023). Age, sex, genetics, environmental factors and metabolic disorder also become a cause of forming urinary tract stones.…”
Section: Discussionmentioning
confidence: 99%
“…Urolithiasis is the condition in which stones are formed in the urinary tract due to elevated levels of salts in urine. According to studies, almost 2% individuals in their 20s and 30s develop kidney stones (Stamatelou and Goldfarb, 2023). Age, sex, genetics, environmental factors and metabolic disorder also become a cause of forming urinary tract stones.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study assessed the validity of ICD-9 codes for upper urinary tract stone disease and reported a high positive predictive value (95.9%). 19 Secondary outcomes included nephrolithiasis diagnosed in the (1) inpatient setting with a claims code in any position; (2) inpatient setting with a claims code in the primary position; and (3) any setting (inpatient or outpatient) with a claims code in any position, the additional requirement of a nephrolithiasisrelated procedure code (eTable 1 in Supplement 1) within 90 days of the diagnosis, and the outcome date being the date of the nephrolithiasis claims code.…”
Section: Key Pointsmentioning
confidence: 99%
“…T he prevalence of kidney stones has been increasing in the US, rising to 10.1% in 2015-2016, 1 and is increasing worldwide. 2 Kidney stones are associated with substantial costs (>$10 billion annually in the US 3 ), as well as kidney function decline, 4,5 cardiovascular disease, 6 and fractures. 7 Type 2 diabetes (T2D) is associated with an increased risk of kidney stones.…”
mentioning
confidence: 99%
“…Nephrolithiasis is now recognized as a complex disease linked to other systemic conditions rather than a benign urinary disorder. Numerous epidemiological studies have demonstrated a correlation between nephrolithiasis and other systemic diseases such as obesity, metabolic syndrome (Wong et al, 2016), diabetes, hypertension, cardiovascular disease and chronic kidney disease (Stamatelou & Goldfarb, 2023). Silkworms are a good model for studying calcium oxalate crystallization in malpighian tubules (MT) as silkworms accumulate a large amount of calcium oxalate crystals in their malpighian tubules during their larval development from first instar to fifth instar without doing any harm to their body.…”
Section: Potential For Kidney Stone Researchmentioning
confidence: 99%